Optimizing Oncology Generic Medication Selection in the Gulf Region: Expert Consensus and MCDA Tool Development - Anas Hamad; Omar AbdulAziz; Osama Abu Tabar; Sara Al Balushi; Sana Alblooshi; Mohamad Alfar; Eren Dawoud; Fahmeeda Khan; Abdulrahman Nabeel; Wael Sayam; Ahmad ElSheashaey (Journal of Health Economics and Outcomes Research)
# Background Cancer remains a leading global health challenge, with high mortality rates and increasing financial burdens on healthcare systems. In the Gulf Cooperation Council countries, generic oncology medications offer a cost-effective alternative to patented treatments. However, disparities in regulatory frameworks and concerns about quality and supply reliability hinder their widespread adoption. Addressing these challenges is crucial to ensuring optimal access to oncology treatments.